2004
DOI: 10.1213/01.ane.0000130261.90896.6c
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Awareness During Anesthesia: A Multicenter United States Study

Abstract: Awareness with recall after general anesthesia is an infrequent, but well described, phenomenon that may result in posttraumatic stress disorder. There are no recent data on the incidence of this complication in the United States. We, therefore, undertook a prospective study to determine the incidence of awareness with recall during general anesthesia in the United States. This is a prospective, nonrandomized descriptive cohort study that was conducted at seven academic medical centers in the United States. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
376
12
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(422 citation statements)
references
References 24 publications
20
376
12
14
Order By: Relevance
“…Our study is consistent with a study of Sebel, et al from the US which showed that an incidence of intra-operative awareness of about 0.1% to 0.2% of patients undergoing general anesthesia [22]. Our study is also in line with a study from Europe that a large prospective study conducted by Samuelsson et al who explored awareness of 11,785 patients undergoing general anesthesia.…”
Section: Bis-guided Anesthesia Can Reduce the Risk Of Intra-operativesupporting
confidence: 93%
See 1 more Smart Citation
“…Our study is consistent with a study of Sebel, et al from the US which showed that an incidence of intra-operative awareness of about 0.1% to 0.2% of patients undergoing general anesthesia [22]. Our study is also in line with a study from Europe that a large prospective study conducted by Samuelsson et al who explored awareness of 11,785 patients undergoing general anesthesia.…”
Section: Bis-guided Anesthesia Can Reduce the Risk Of Intra-operativesupporting
confidence: 93%
“…These results are in line with Sebel et al who showed that age and gender did not affect the incidence of awareness [52]. In the contrary, a study of Katoh et al found that age strongly affected BIS points.…”
Section: Awareness and Gender Surgical Time And Agesupporting
confidence: 90%
“…In turn, anesthetics are currently being used as powerful probes to gain fundamental insights into the biology and neuronal substrates of memory. Such insights may allow the development of strategies to prevent and treat memory disorders associated with anesthetic states, such as intraoperative awareness [149][150][151] and memory deficits in the postoperative period. [152][153][154] …”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used electroencephalographic (EEG) device for monitoring the level of sedation during anesthesia is the bispectral index (BIS) monitor [1]. This device has been extensively studied and validated over the past 10 years in adult and pediatric cardiac anesthesia [2].…”
Section: Introductionmentioning
confidence: 99%